2021
DOI: 10.1038/s41467-020-20630-1
|View full text |Cite
|
Sign up to set email alerts
|

Heme-binding enables allosteric modulation in an ancient TIM-barrel glycosidase

Abstract: Glycosidases are phylogenetically widely distributed enzymes that are crucial for the cleavage of glycosidic bonds. Here, we present the exceptional properties of a putative ancestor of bacterial and eukaryotic family-1 glycosidases. The ancestral protein shares the TIM-barrel fold with its modern descendants but displays large regions with greatly enhanced conformational flexibility. Yet, the barrel core remains comparatively rigid and the ancestral glycosidase activity is stable, with an optimum temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 72 publications
0
38
0
1
Order By: Relevance
“…These are discussed in more detail in the subsequent section. However, as some (of many) other examples of recent success stories, ASR has been used to understand allosteric communication in a multienzyme complex of a key metabolic enzyme, tryptophan synthase [32,33], to obtain a high-redox-potential laccase [34], to modulate the catalytic adaptability of an extremophile kinase [35], and to identify novel heme binding that modulates the allosteric regulation of an ancestral glycosidase (Figure 1) [36]. This latter study is notable as heme binding was not observed in any of ~5500 crystal structures of ~1400 modern glycosidases.…”
Section: Repurposing Ancient Enzymes For New Catalytic Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are discussed in more detail in the subsequent section. However, as some (of many) other examples of recent success stories, ASR has been used to understand allosteric communication in a multienzyme complex of a key metabolic enzyme, tryptophan synthase [32,33], to obtain a high-redox-potential laccase [34], to modulate the catalytic adaptability of an extremophile kinase [35], and to identify novel heme binding that modulates the allosteric regulation of an ancestral glycosidase (Figure 1) [36]. This latter study is notable as heme binding was not observed in any of ~5500 crystal structures of ~1400 modern glycosidases.…”
Section: Repurposing Ancient Enzymes For New Catalytic Functionsmentioning
confidence: 99%
“…This latter study is notable as heme binding was not observed in any of ~5500 crystal structures of ~1400 modern glycosidases. Experimental characterization of a number of modern glycosidases showed appreciable levels of heme binding but significantly lower than that of the ancestral glycosidase, indicating that the ability to efficiently bind heme to allosterically regulate catalysis is a specific feature of the ancestral enzyme [36].…”
Section: Repurposing Ancient Enzymes For New Catalytic Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancestral sequence reconstruction has been amply used in the post-genomic era as a tool to address fundamental problems in molecular evolution [ 3 , 4 , 5 ]. Furthermore, it has been found that ancestral proteins that are “resurrected” in the lab (i.e., the proteins encoded by the reconstructed sequences) often display interesting and even extreme properties [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] that, plausibly, reflect ancestral adaptations to unusual intra- and extra-cellular environments. Resurrected ancestral proteins often display high stability, supporting the frequently hypothesized thermophilic nature of ancient life.…”
Section: Introductionmentioning
confidence: 99%
“…El descubrimiento de nuevos materiales conocidos como nanomateriales o biomateriales cuya función es recrear o formar tejidos funcionales a partir del control celular gracias a su capacidad de organizarse, crecer, diferenciarse y formar una matriz funcional bajo condiciones controladas (Bai, Gao, & Syed, 2018). Estas condiciones se combinan en un complejo proceso orgánico que requiere señales endocrinas, hormonales, químicas, de diferenciación, de posición o interacciones entre las células y la matriz para mediante fuerzas mecánicas se logre la formación de una estructura en 3 dimensiones completamente funcional (Gamiz, et al, 2021;Morales, 2014).…”
Section: Introductionunclassified